Strategi Mitigasi Pinjaman Online Berbasis Literasi Keuangan Syariah (Penelitian Kasus Mahasiswa Institut Syekh Abdul Halim Hasan Binjai) - Zahira, Fitri Nada; Barus, Elida Elfi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The purpose of this study is to determine the understanding of online loan mitigation strategies based on Islamic financial literacy in INSAN Binjai students. The research method used in this study is qualitative. The population in this study is all INSAN Binjai students. The sample used in this study is students and professionals of the sharia economics study program with certain considerations. The data collection techniques used are interviews and documentation. Interviews were conducted with INSAN Binjai students and Islamic finance professionals. The analysis technique used is SWOT analysis. The results of the study show that there are four suggested approaches to solve the problem of online loans: (1) Holding Islamic financial literacy programs, such as seminars and training, (2) Using social media to disseminate information, (3) Establishing Islamic microfinance institutions that offer education financing, such as installment schemes with affordable margins or Qardhul Hasan contracts (benevolent loans) and (4) Providing counseling services for individuals facing this problem. It is hoped that this method will increase students' knowledge of finance, reduce the use of online loans, and encourage Islamic-based financial management